EFFECTS OF AN EDUCATIONAL INTERVENTION ON KNOWLEDGE AND SAFETY PRACTICES IN PESTICIDE HANDLING AMONG FARMERS IN SAMARAHAN, SARAWAK - Lim, Siong Hee; Helmy, Hazmi; Cheah, Whye Lian (Malaysian Public Health Physician's Association, 2023)
Poor safety practices in pesticide handling contribute to the severe consequences of cases of pesticide poisoning globally. The objective of this study was to determine the effectiveness of an educational intervention to improve the knowledge and safety practices in pesticide handling among farmers in Samarahan, Sarawak. A quasi-experimental study was conducted involving an interventional (n= 50) and a control group (n = 50). A self-administered questionnaire was used to collect baseline information on participants’ knowledge and practices in pesticide handling. Participants in the interventional group underwent a five-month interventional programme consisting of four modules on the importance of understanding pesticides label, short and long-term effects of pesticides, routes of entry into the body and symptoms manifested upon exposure, safety usage, storage and disposal methods and practices. The control group were not exposed to any intervention. All the participants were reassessed at one- and fifth-month post-intervention using a validated self-administered questionnaire. Data were analysed using repeated measure analysis of variance to measure the effect of intervention between the groups. No significant difference was observed in the baseline based on gender and age distribution between both groups. Participants from the interventional group recorded a significant improvement in the mean knowledge and safety practices scores in the first month and fifth months compared to the baseline values. Meanwhile, no significant improvement in both outcomes was detected in the control group throughout the three assessments. These findings revealed that locally tailored educational intervention is effective in improving the knowledge level and safety practices of farmers in pesticide handling. Hence, these findings can be used by local authorities to develop an effective intervention for pesticide users in Sarawak and other states in Malaysia in reducing the risk of pesticide exposure. Keywords: Farmers, pesticide poisoning, educational intervention, safety practices, knowledge